Matching Variables with the Appropriate Statistical Tests in Counseling Research - Ryan E Flinn; Michael T Kalkbrenner (Teaching and Supervision in Counseling, 2021)
Quantitative research literacy, including matching variables with the appropriate statistical tests, is a key element in counselor education and preparation. Counselor educators are tasked with teaching quantitative research and statistics, which counselors-in-training tend to find anxiety-producing. Authors aimed to provide a succinct overview of matching variables with appropriate statistical tests and provide strategies counselor educators can use to enhance their pedagogy.
Keywords: Counselor preparation; quantitative research; research question; variables; statistics